Osteomyelitis as a Result of Pancreaticojejunostomy Stent Migration after Whipple Procedure. Issue 1 (2018) - Munis, Assad; Solomon, Brad; Mazulis, Andrew; Laurie, Timothy
ABSTRACT : N/A: Pancreaticoduodenectomy, or Whipple procedure, is a high‐risk surgical procedure commonly performed for tumors of the pancreatic head. The pancreatico‐enteric anastomosis is an important component of this procedure. The maturation and adequate healing of this anastomotic site is critical to decrease the risk of postoperative pancreatic fistulas. The use of stents can help in the healing of this anastomotic site. We present a patient with pancreatic adenocarcinoma who underwent pancreaticoduodenectomy, and presented with progressively worsening lumbar pain 7 years later. The patient was found to have osteomyelitis as a complication from an enterospinal fistula secondary to a migrated pediatric feeding tube that was placed at the pancreaticojejunal anastomosis.